From Structure to Diagnosis in medical education: An Analysis of Linguistic Features in Iranian Medical Reporting - Mahboub Amani; Nader Asadi; Masoud Zoghi (Future of Medical Education Journal)
Background:  Technological progress in medicine necessitates linguistic analysis of diagnostic reports. This study explores the linguistic functions of medical diagnostic reports, by focusing on Radiology Case Reports (RCRs), Magnetic Resonance Imaging (MRI) reports, and Computed Tomography-Scan (CT-scan) reports.Method: This descriptive study analyzed a corpus of 300 diagnostic medical reports from Tabriz Medical Science University over a three-month period (Autumn 2024). By employing Rhetorical Structure Theory (RST) postulated by Mann and Thompson, this study emphasizes the functional aspects of language by analyzing how linguistic choices fulfill communicative purposes within specific contexts. RST provides a systematic approach to identifying the relationships between different sections of a text, offering insights into how diagnostic reports are organized to convey medical findings clearly and effectively.Results: Diagnostic reports exhibited a predominance of nominal groups (75%), highlighting their critical role in providing detailed identification of anatomical structures. Prepositional groups accounted for 10%, primarily used to offer spatial and procedural context. Verbal groups in passive voice made up 15%, reflecting objectivity and focus on findings and procedures. Complex clauses appeared in 60% of the reports, integrating diagnostic observations concisely. Conciseness was prevalent in 80% of the cases, ensuring that reports were brief yet informative. This highlights a focus on clarity, precision, and efficiency through structured, objective language.Conclusion: These linguistic features serve as important teaching points in medical education for improving students’ competencies in writing and interpreting diagnostic texts that can prepare future healthcare professionals to produce diagnostically effective and professionally appropriate medical documentation.